St-elevation myocardial infarction systems of care in Africa - Pool, Albertus Johannes (Division of Emergency Medicine, 2025)
Objectives: The aim of the study is to describe and summarise the body of literature pertaining to ST-Elevation Myocardial Infarction Systems of Care (STEMI SOC), as well as barriers and solutions to STEMI SOC implementation in the African context. Methods: The Scoping Review has been designed following the PRISMA-ScR Guidelines. The search strategy consisted of three elements: STEMI Systems of Care, STEMI, and Africa. These three elements were combined to compile a comprehensive search strategy to answer the main research question. EbscoHost, Medline via PubMed, and Google Scholar databases were searched. All study types that collected primary data or that ran an analysis on an existing data set, conference abstracts, reports, and unpublished ‘grey' literature were included. Studies not in English and where a full text was not available were excluded. Two reviewers independently assessed the studies for eligibility based on title, abstract, and full text. Included full-text articles were interrogated in the same manner. Data was extracted from the included literature and were subjected to descriptive analysis to develop a summary description of the main themes. Results: A total of 656 articles were identified through the database search, 607 articles were excluded after duplications removal and full text screening. A total of 49 articles met the inclusion criteria for full review. The articles originated from studies conducted in South Africa 39%, Egypt 12%, Kenya 10%, Tunisia 10%, Ethiopia 8%, Ivory Coast 6%, Cameroon 4%, and one study each from Sudan, Tanzania, Libya, Nigeria, and the combined Maghreb Region. The literature on STEMI systems of Care in Africa is scarce with only Egypt, Tunisia, and South Africa reporting some information on their systems. STEMI patients in Africa are generally younger than their Western counterparts, present late to healthcare facilities, have low education levels, insufficient healthcare insurance, and are non-adherent to discharge medication. Emergency Medical Services are lacking, there's a shortage of PCI-facilities, EDs are disorganised, STEMI reperfusion times are delayed, data collection and quality assurance initiatives are inadequate, and STEMI referral networks and -registries are left wanting. In addition, there's a deficiency of ECG and telemetry, a shortage of healthcare workers, a lack of adherence to guideline recommended therapy, and a perceived hesitancy of medical personnel to administer fibrinolytics, suggestive of a need for more clinical education. Conclusion: A myriad of barriers has been reported in this review, as well as potential facilitators in the implementation of these networks. The coordination and introduction of a STEMI Systems of Care in African settings potentially holds great advantages as has been witnessed in other LMICs and HICs.